IT CULTURAL HERITAGE: PRESERVATION AND MAKING IT AVAILABLE AS SEEN FROM THE PERSPECTIVE OF THE MUSEUM OF THE HISTORY OF COMPUTERS AND IT IN KATOWICE - Małgorzata Pstrocka-Rak (Index Copernicus International S.A., 2021)
It is the biggest museum of IT technologies in Poland: Museum of the History of Computers and IT in Katowice (MHKI) that the paper is dedicated to. The trend to create this kind of museums has been observed in technologically- advanced countries for over 20 years. It is connected with the shift in perceiving technological accessories of a daily life, which have been gradually incorporated into the circle of cultural heritage, and subsequently covered with institutional protection. Founders of such museums generally rank among private entities and private individuals motivated by their passion to preserve and popularize technological heritage among the present and future generations. What IT museums worldwide have in common is the rarely encountered in classical museology model of allowing visitors a direct interaction with the exhibits. At the same time, these museums are market operators, which, apart from culture- -forming activity, forces them to achieve their autonomy and financial stability first of all owing to the visitor turnout and partnership contracts with outside entities: companies and the media. All these issues were the topic of an extensive interview with MHKI’s Director which provides the material for the paper. The acquired information may serve as a source of knowledge and inspiration for potential founders of other IT heritage museums to be established in Poland.